PERBEDAAN KOMUNIKASI TERAPEUTIK ORAL PHYSIOTHERAPY DENGAN PANDUAN DAN TANPA PANDUAN TERHADAP TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT SISWA SMPN 1 MARGA KABUPATEN TABANAN TAHUN 2020 - Ni Nyoman Dewi Supariani; Ni Nengah Sumerti (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
The promotion of oral health in adolescents can be done through counseling both individually and in groups. One of the communications that can be used in dental care is therapeutic communication. Methods used by patients for oral hygiene include oral physiotherapy.The purpose of this study was to determine the differences in oral physiotherapy therapeutic communication with guidance and without guidance on the level of knowledge about oral health of students at SMPN 1 Marga, Tabanan Regency in 2020. The study was conducted with an experimental design: pre post test with control design. The number of research samples was 130 people. Analysis of Paired Sample t-Test there was an increase of 18.5% in the level of knowledge with very good criteria and 10.8% with good criteria and there were still students with failure criteria as much as 3.1% on the post-test scores after being given therapeutic communication oral physiotherapy without guidance, while the group of students who got the guidance there was an increase of 29.2% in the level of knowledge with very good criteria and there were still students who failed criteria as much as 1.5% on the post test score. There was a significant difference between communication therapeutic oral physiotherapy with guidance and without guidance with a value of p = 0.00.